ANALISIS STATUS MUTU BATANG AGAM BAGIAN TENGAH - Desi Widia Kusuma (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2016)
Batang Agam River that flows through Agam Regency, Bukittinggi City, Payakumbuh City and Limapuluh Kota Regency is the river which plays an important role because it is set as the target of Minimum Service Standards (SPM) of the environmental field in Province. Yet, the quality is likely to decline due to pollution. This study aims to know the description of wastewater treatment of Slaughter House (RPH) of Bukittinggi were suspected as one pollutant sources and to analyze the water quality statues of Batang Agam River in the middle segment. This is a descriptive quantitative study using secondary data of water quality of Batang Agam River from Bapedalda of the Province of West Sumatera Year 2015. The method that used to determine the quality status is Pollution Index. From the results of the study known that the wastewater treatment of Slaughter House is not eligible. Pollution parameters of Batang Agam River in the middle section are : BOD, COD, NH3, Total Coliform and Fecal Coliform. Total Coliform and fecal Coliform already on heavy polluted status for all monitoring locations.